EXPERIMENTAL STUDY OF THE CONVECTIVE HEAT TRANSFER FROM TUBES WITH VARIOUS CROSS-SECTION - Muhammad Chrissandy Fahzy; Yonas Paskah Pardede; Danel Reka Yesa; Mohd Raden Bahi; Kaprawi Sahim (Indonesian Journal of Engineering and Science (IJES), 2022)
In heat transfer engineering, most of the tubes of the circular cross-section are used in the heat exchanger application, but the possibilities of using tubes other than circular type are available to enhance the rate of heat transfer. This experimental study presents the heat transfer rate performance of the tubes' difference cross-section; circular, elliptic, square, and triangle tubes. The tubes were heated at uniform heat flux at the outside surface, and the water flowed inside the tubes. The important parameters were measured during the experimentation. The results show that the heat transfer varies with the cross-section type. The triangle and elliptical tube give a higher heat transfer rate than other cross-sections.